2015
DOI: 10.1073/pnas.1422487112
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic reconfiguration of frontal brain networks during executive cognition in humans

Abstract: The brain is an inherently dynamic system, and executive cognition requires dynamically reconfiguring, highly evolving networks of brain regions that interact in complex and transient communication patterns. However, a precise characterization of these reconfiguration processes during cognitive function in humans remains elusive. Here, we use a series of techniques developed in the field of "dynamic network neuroscience" to investigate the dynamics of functional brain networks in 344 healthy subjects during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

62
723
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 719 publications
(809 citation statements)
references
References 62 publications
62
723
2
1
Order By: Relevance
“…Crucially, connector nodes are also not involved in all betweenmodule connectivity. Nonconnector node regions play a role as well (28,87,93,94), and, as noted above, increased betweenmodule connectivity that is not routed through connector nodes has been found during many different tasks, and differentiates task connectivity from resting-state connectivity (36). Although the current and previous findings suggest that connector node regions coordinate some of these between-module connections, it is likely that other mechanisms for between-module communication exist that are executed by nonconnector nodes.…”
Section: Discussionmentioning
(Expert classified)
See 2 more Smart Citations
“…Crucially, connector nodes are also not involved in all betweenmodule connectivity. Nonconnector node regions play a role as well (28,87,93,94), and, as noted above, increased betweenmodule connectivity that is not routed through connector nodes has been found during many different tasks, and differentiates task connectivity from resting-state connectivity (36). Although the current and previous findings suggest that connector node regions coordinate some of these between-module connections, it is likely that other mechanisms for between-module communication exist that are executed by nonconnector nodes.…”
Section: Discussionmentioning
(Expert classified)
“…Although the current and previous findings suggest that connector node regions coordinate some of these between-module connections, it is likely that other mechanisms for between-module communication exist that are executed by nonconnector nodes. In line with this, connector nodes are not the only nodes that change module membership during tasks (87,93). For example, an fMRI study of a 2-back task showed that, although many connector node regions changed module membership and this predicted higher performance, the regions with the most module membership changes were in ventromedial prefrontal cortex, where no connector nodes were located in our analysis (93).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The architecture of the human brain is intrinsically organized into time-varying assemblies of functionally interacting nodes (16,18), a dynamic neural community structure allowing for high adaptability of the system to changing environmental demands (29). Schizophrenia is increasingly recognized as a heritable brain disorder with altered neural network dynamics, yet the presence of alterations in the time-varying configuration of the functional connectome and their genetic and pharmacological implications require clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the "static" network approaches, these methods allow for the quantification of contextdependent changes of the network community structure over time (e.g., during learning or cognitive load), which is arguably a biologically more accurate description of normal and disordered brain network dynamics (16,18,19). Moreover, the temporal variability of the neural community structure predicts learning (16) and executive function (18) in normal volunteers, which are two established deficit areas in schizophrenia (20,21). The temporal dynamic thus appears to reflect the capacity of the brain connectome to configure flexibly in support of cognitive demands, a feature that may relate to the genetic risk architecture of schizophrenia.…”
mentioning
confidence: 99%